Roles of health system leadership under emergency in drought-affected districts in northeast Uganda: a mixed-method study - Charles Njuguna; Habteyes Tola; Benson Ngugi Maina; Kwikiriza Nicholas Magambo; Samalie Namukose; Sarah Kamau; Yonas Tegegn Woldemariam (BMJ Open, 2024)
Objective Health system leadership plays a critical role in sustaining healthcare delivery during emergencies. Thus, we aimed to assess the contribution of health system leadership in sustaining healthcare delivery under emergency conditions based on adaptive leadership theoretical framework.Design We employed a concurrent mixed-methods study approach to assess health system leadership roles during emergency. This involved a quantitative survey administered to 150 health facilities managers/service focal persons selected via multistage sampling method from 15 districts, and qualitative interviews with 48 key informants who purposively selected.Participants We interviewed health facility managers, services focal persons, district health officers and residential district commissioners. We also reviewed weekly emergency situation reports and other relevant documents related to the emergency response. We used structured questionnaire, observation checklist and semistructured questionnaire to collect data. We employed descriptive statistics to analyse quantitative data and thematic analysis for qualitative data.Main outcome Health system leadership contributions in sustaining healthcare delivery during emergencies.Results Health system leadership was effective in leading emergency response and ensuring the continuity of health service during emergencies. Community engagement, partners coordination and intersectoral collaboration were effectively used in the emergency response and ensuring continuity of healthcare delivery. Deployment of experienced personnel and essential medical and non-medical supplies played a critical role in the continuity of health service. Availability of incidence management teams across health system significantly contributed to health system leadership. Participation of village health teams in community engagement and information communication helped in the success of health system leadership under emergency.Conclusion Adaptive health system leadership played a crucial role in managing health services delivery under emergency conditions. Effective partnership coordination and collaboration across sectors, frequent information communication, building local actor capacity and implementing scheduled supportive supervisions emerged as key strategies for sustaining health services during emergencies.